2021
DOI: 10.2478/johr-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biostimulants on Tomato Plants Cultivated under Hydroponic Systems

Abstract: Two biostimulants, RutfarmMaxifol (Ascophyllum nodosum extract 17.5%, amino acids, macro- and microelements, Agromaster, Russia) and Radifarm (polysaccharides, glycosides, amino acids, and micro-elements; Valagro, Italy), were applied at different concentrations on tomato plants of the hybrid cultivar ‘Merlice’, grown under a hydroponic system. Biostimulants were applied in the form of seed soaking and twice as foliar sprayings at flowering and at the initial fruit development stages. Biostimulants were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The research carried out in this study regarding titratable acidity showed that although there are no significant differences between the experimental variants (Figure 4), the acidity is lower (between 1.13 ± 0.30 and 1.19 ± 0.19 g% citric acid) in the tomato fruit from treated plants than in the control variant (1.38 ± 0.18 g% citric acid). Also, according to Abdelkader et al [33], the acidity rate of the tomato fruit tended to decrease under biostimulant treatment. The low acidity of tomato fruit is involved not only in defining the taste and flavor, but also has an important contribution to food safety by destroying spoilage microorganisms [35].…”
Section: Influence Of Biostimulant Treatment On the Nutritive Compoun...mentioning
confidence: 94%
See 2 more Smart Citations
“…The research carried out in this study regarding titratable acidity showed that although there are no significant differences between the experimental variants (Figure 4), the acidity is lower (between 1.13 ± 0.30 and 1.19 ± 0.19 g% citric acid) in the tomato fruit from treated plants than in the control variant (1.38 ± 0.18 g% citric acid). Also, according to Abdelkader et al [33], the acidity rate of the tomato fruit tended to decrease under biostimulant treatment. The low acidity of tomato fruit is involved not only in defining the taste and flavor, but also has an important contribution to food safety by destroying spoilage microorganisms [35].…”
Section: Influence Of Biostimulant Treatment On the Nutritive Compoun...mentioning
confidence: 94%
“…The same trend was noted regarding total soluble sugars, which registered an increase of 22% in the V2 sample and 39% in the V3 sample, compared to the untreated sample (Figure 4). Also, Abdelkader et al [33] reported enhanced dry matter of tomato fruit by 14% over control (from 6.35% to 6.85%) under biostimulant treatment. On the contrary, investigating the effect of three biostimulants applied on a tomato crop, Grabowska et al [34] found that there was no clear effect of biostimulants on the dry substance and soluble sugar amount in the tomato fruit.…”
Section: Influence Of Biostimulant Treatment On the Nutritive Compoun...mentioning
confidence: 99%
See 1 more Smart Citation
“…The following parameters were measured at 90 DAT: chlorophyll content (chlorometer), acidity, total soluble solids (refractometer), and ascorbic acid content (vitamin C). Ascorbic acid was measured via methods described by the Association of Analytical Communities, particularly the 2,6-dichlorophenol indophenol titration method, and expressed as mg•100 g −1 FW [37]. To measure titratable acidity (TA), tomato fruits were homogenized with distilled water and then titrated with 0.1 N NaOH.…”
Section: Physio-biochemical Attributesmentioning
confidence: 99%
“…Biostimulants are considered bioactive substances that are either inorganic or organic microorganisms that can increase crop performance when utilized in small quantities [ 1 ] as they can enhance both performance and growth as well as improve nutrient- and water-use efficiencies of different crops [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Amino acids have a dual function as building blocks for proteins and as providers of organic nitrogen, which can alleviate the negative impacts of drought and salt stress [ 9 ], and promote cell growth. They are vital in metabolite synthesis, growth, and development, and appropriate in plants because of their structure as protein units [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%